Motivasi Pemandu Wisata Terkait Pay as You Wish Walking Tours di Bandung Good Guide - Nanlohy , Arzeta Bilbeana; Martono, Ecklesia Femmy Eideltraut; Billah , Nidzam Baldan; Retno Syafitri; Subandi, Mohamad Robbith (Politeknik Pariwisata NHI Bandung, 2024)
The motivation of tour guides can be influenced by various factors, such as job satisfaction, financial incentives, and social interaction. This study aims to examine the motivation of tour guides at Bandung Good Guide under the Pay As You Wish payment system. The author employs a qualitative approach, conducting in-depth interviews with experienced tour guides who have led tours for Bandung Good Guide. The findings will reveal the motivational factors influencing tour guides at Bandung Good Guide within the Pay As You Wish framework. This research holds significant implications for tour guides in the travel industry, particularly in promoting sustainable tourism through walking tours